-1=u-2

Simple and best practice solution for -1=u-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1=u-2 equation:


Simplifying
-1 = u + -2

Reorder the terms:
-1 = -2 + u

Solving
-1 = -2 + u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-1u' to each side of the equation.
-1 + -1u = -2 + u + -1u

Combine like terms: u + -1u = 0
-1 + -1u = -2 + 0
-1 + -1u = -2

Add '1' to each side of the equation.
-1 + 1 + -1u = -2 + 1

Combine like terms: -1 + 1 = 0
0 + -1u = -2 + 1
-1u = -2 + 1

Combine like terms: -2 + 1 = -1
-1u = -1

Divide each side by '-1'.
u = 1

Simplifying
u = 1

See similar equations:

| 52=-2(22-x)+4(x-3) | | 32x^2+18=0 | | (a+1)*(a-3)x=(a+1)*(a+4) | | .8(220-a)=120 | | 2(1+v)=-6+4v | | 117+7y=180 | | 9x^2-18xy-8x+16y=0 | | 15n-6n= | | 3s+s=-49 | | -9.8(27x-65)=78.24(6x+34) | | 4(x-5)-2(x+2)=-22 | | 3e-4=-2 | | 2+14a=-8+9a | | 7y+18=180 | | 60x^2-20xy+12x=0 | | -7(a-6)=2-2a | | 4(x-3)=2x+2(x-6) | | 2x^6-17x^4+17x^3= | | 15x+45=180 | | ba-4b=c | | .5x+3=2 | | 6x^3-9x^2-216x+9=0 | | 25=-8+2(s-4) | | 3(a+b)=f | | 35x^2-9x-2=0 | | (-6x+7)=(19x-1) | | 9y+4-7y=124 | | -10(x-1)=-10x | | 0=4x^2+39x-10 | | -5b+6(1-b)=83 | | 2x^4-x^3-9x^2+13x-4=0 | | y-5=7(x-6) |

Equations solver categories